Propiedades mecánicas de laminados estructurales con madera de encino - Ordóñez Candelaria, V. Rubén; Quiroz Soto, Arturo; Zarate Morales, Reyna Paula (Instituto de Ecología, A.C., 2016)
Oakwood (Quercus sp) is a very important forest resource in México, but its use is very reduced. In order to provide options to increase the utilization of oakwood, this paper presents the procedures of fabrication of nine oakwood glue laminated beams, which were tested in bending and the mechanical properties obtained are presented. Two species were collected and sawn to make the gluelaminated beams, for both species their physical and mechanical properties were determined making tests on small clear specimens. Four trees were collected at the Cofre de Perote, three of Quercus laurina and one of Quercus crassifolia.